The impact of teacher competence on learning outcomes in university flipped classroom teaching - Wang, Hao; Hamid, Junainah Abd; Tham, Jacquline (Edelweiss Applied Science and Technology, 2026)
With the deepening of higher education teaching reform, the flipped classroom, as a new teaching model, is gradually replacing traditional rote learning and becoming an important path to improve the quality of university teaching. Since the researchers aim to clarify the relationship between teacher competence and learning outcomes in flipped classroom implementation in higher education institutions in Shanxi Province, China, the purpose of this study can be summarized as hypothesis testing. Through stratified random sampling, the study covers 10 undergraduate institutions in Shanxi Province. Data was collected using a Likert scale, and a student learning efficacy scale was designed to address the research questions. Research has found that teacher competence has a direct impact on teaching effectiveness, but different teacher competencies have varying degrees of impact on the various dimensions of learning outcomes. This paper defines the core dimensions of teacher competence, analyzes the mechanism by which teacher competence affects student learning outcomes, and verifies the correlation between the two through empirical analysis. This provides theoretical support and practical reference for improving flipped classroom teaching practices and building a strong teaching force in higher education institutions.